1992
DOI: 10.1111/j.1600-0773.1992.tb00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Nephrotoxicity in Rat: Some Biochemical Correlates

Abstract: The present work examines the effect of treatment of rats with graded doses of the aminoglycoside antibiotic gentamicin on the concentration of reduced glutathione (GSH) and diamine oxidase (DAO) activity in the kidney, and DAO activity, creatinine and magnesium (Mg) in the plasma. The animals were given the antibiotic intramuscularly in doses of 20, 40, and 80 mg/kg/day for 6 days, and were killed 24 hr after the last injection. In another experiment rats were injected intramuscularly with gentamicin at a dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Researchers also observed that creatinine (Cr) level is a more accurate measurement for glomerular impairment than urea levels/Cr clearance. [42,43] Our study results coincide with earlier reports that a significant increase in plasma urea and creatinine or decrease in potassium levels [40,41,44] might indicate a nephrotoxic condition in GEN-treated rats and may be due to kidney damage caused by the enhanced generation of ROS. These findings correlated well with the renal histological examination, which revealed renal tubular necrosis and interstitial nephritis.…”
Section: Discussionsupporting
confidence: 82%
“…Researchers also observed that creatinine (Cr) level is a more accurate measurement for glomerular impairment than urea levels/Cr clearance. [42,43] Our study results coincide with earlier reports that a significant increase in plasma urea and creatinine or decrease in potassium levels [40,41,44] might indicate a nephrotoxic condition in GEN-treated rats and may be due to kidney damage caused by the enhanced generation of ROS. These findings correlated well with the renal histological examination, which revealed renal tubular necrosis and interstitial nephritis.…”
Section: Discussionsupporting
confidence: 82%
“…GM nephrotoxicity is, at least partially, attributed to the generation of free radicals, enhanced lipid peroxidation, and decreased glutathione (GSH), in the kidney (Ramsammy et al, 1985;Walker & Shah, 1988;Ali et al, 1992). It is reasonable, therefore, to suggest that the observed nephroprotective action of the date flesh and pits may be due to an increase in activity of the free radical scavenging enzymes or counteraction of the free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the antibiotic's nephrotoxicity therefore has substantial clinical significance [1]. But early detection of renal damage is difficult.…”
Section: Introductionmentioning
confidence: 99%